Minimal Residual Disease in Multiple Myeloma: Ready for Prime Time?. Issue 3 (May 2021) - Mina, Roberto; Bonello, Francesca; Oliva, Stefania
Abstract : Abstract: Minimal residual disease (MRD) techniques are essential to identify the small clonal fraction within and outside the bone marrow. In the last years, evidence regarding their prognostic role for the evaluation of the depth of response of current treatment strategies has grown rapidly. Consequently, MRD was incorporated in an increasing number of clinical trials for multiple myeloma patients, also as primary endpoint, and even to guide therapeutic choices. A robust correlation between MRD negativity and survival was established. Yet, several issues regarding MRD evaluation remain to be addressed: from the optimal and more cost-effective techniques for its assessment and its harmonization worldwide to its use in clinical practice to its impact on treatment modulation. This review focuses on the available evidence supporting the use of MRD status for the management of multiple myeloma patients and on open issues that still need an answer.